COMPARISON OF POSITIONING BETWEEN SEMI-FOWLER'S AND LEFT LATERAL TO OXYGEN SATURATION IN VENTILATED PATIENTS: A QUASI-EXPERIMENTAL STUDY: COMPARISON OF POSITIONING BETWEEN SEMI-FOWLER'S AND LEFT LATERAL TO OXYGEN SATURATION IN VENTILATED PATIENTS: A QUASI-EXPERIMENTAL STUDY - Musri; Nuraeni Yudistirawati (Politeknik Kesehatan Kemenkes RI Jakarta I, 2021)
Background: In Insentive Care Unit, generally the patients use a mechanical ventilator, so intensive monitoring is necessary, including one of which is oxygen saturation. Regular patient positioning in the ICU need to prevent complications. Giving the position of the body can affect the development of the lung and thoracic wall which affects lung volume and gas exchange. The research objective: to determine the comparison of positioning of the semi-fowler head elevation of 300 and left lateral both head elevation of 300 to the increase in oxygen saturation in patients on a ventilator in the ICU. Methodology: quasi experiment use pretest- posttest with control group. The total of sample was 30 patients divided into 15 patients in the 300 semi-fowler’s position and 15 patients in the left lateral with 30? Head Elevations. Oxygen saturation data was measured using pulse oximetry for all groups. The intervention was carried out 30 minutes three times a day. Data analysis was univariate and bivariate with T test. The results finding: The result showed a significant difference in oxygen saturation before and after interventions. The semi-fowler position with a head elevation of 300 (P value = 0,000) and the left lateral position with a head elevation of 300 (Pvalue = 0.000). The mean increase in oxygen saturation between the semi-fowler and left lateral positions were (P value = 0.006). Conclusion: The left lateral position with a head elevation of 300 was more effective in increasing oxygen saturation in patients on a mechanical ventilator in the ICU. Suggestion: It is expected that the hospital supervises the implementation of giving positions to patients who are admitted to the ICU in a structured and planned manner.